2011
DOI: 10.1177/000348941112000405
|View full text |Cite
|
Sign up to set email alerts
|

Audioprofile-Directed Successful Mutation Analysis in a DFNA2/KCNQ4 (p.Leu274His) Family

Abstract: Familiarity with the audioprofiles of DFNA traits may lead to successful mutation analysis of the gene involved, even in a small family in which genetic linkage analysis is not an option. Alternatively, the specially developed program AudioGene can be accessed on the Internet to perform automatic audioprofile analysis of a family's (audiological) phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…When predictions are complete, results are made available to users online and by e‐mail. Successful application of this website to genetic hearing loss has been demonstrated by the authors and others [ de Heer et al., ].…”
Section: Methodsmentioning
confidence: 99%
“…When predictions are complete, results are made available to users online and by e‐mail. Successful application of this website to genetic hearing loss has been demonstrated by the authors and others [ de Heer et al., ].…”
Section: Methodsmentioning
confidence: 99%
“…AudioGene is a commercially available machine-based audioprofiling system that analyzes audiograms of small families with ADHL to predict the most probable defective genes and loci for mutation screening. However, it is only available for AD patterns of HL [47,52]. Although methods to predict mutated genes in AR pattern of HL have been introduced [51], they are not commercially available yet.…”
Section: Diagnostic Methods and Screeningmentioning
confidence: 99%
“…Later on, it was found that next to mutations in the GJB2 gene, a specific deletion involving part of the GJB6 gene is one of the more frequent alleles (suppl [19][20][21][22]. This deletion has an uneven distribution in different populations; for instance, in China it was found to be present in one population and almost absent in another (suppl 23,24). Although there has been some discussion whether this would present a digenic model, it was proven that the deletion contains a regulatory element for the GJB2 gene; therefore, DFNB1 is a singlegene disorder, with compound heterozygosity instead of double heterozygosity (suppl 25,26).…”
Section: Gjb2 and Gjb6: Dfnb1mentioning
confidence: 99%